The IPRS Image Processing and Pattern Recognition System - Caelli, Terry; Dillon, Craig; Osman, Erol; Krieger, Gerhard (Spatial vision, 1997)
IPRS is a freely available software system which consists of about 250 library functions in C, and a set of application programs. It is designed to run under UNIX and comes with full source code, system manual pages, and a comprehensive user's and programmer's guide. It is intended for use by researchers in human vision, pattern recognition, image processing, machine vision and machine learning.
DLR Import::2019-04-02